A Review of the Application of Biopolymers on Geotechnical Engineering and the Strengthening Mechanisms between Typical Biopolymers and Soils - Jungyeon Jang (Advances in Materials Science and Engineering)
The use of admixtures in soils to improve their properties has been implemented since ancient times. Diverse conventional admixtures such as lime, fly ash, and cement have been added to soils. Also, petrochemicals and bacteria are increasingly used for soil improvement and soil stabilization both mechanically and chemically. However, the conventional admixtures for soils cause significant environmental problems (e.g., CO2 emission). Biopolymers can increasingly replace the conventional admixtures for the application of soil improvement and soil stabilization. Numerous studies have been conducted in the past decades to investigate the suitability and efficiency of various biopolymers for soil improvement. This paper focuses on the properties of the most common biopolymers (xanthan gum, gellan gum, agar, polyacrylamide, and guar gum) and gives the mechanism of biopolymer-treated soils for soil improvements proposed by researchers.